Successful management of bilateral orbital metastases from invasive lobular breast cancer with abemaciclib and letrozole: a case report and literature review - Rodrigues Alves, Nuno; Duarte, Ana Filipa; Ribeiro, David Fernandes; Silva, Rita Sousa; Carvalho, Bruno Almeida; Alpuim Costa, Diogo (Frontiers in Oncology, 2024)
Breast cancer is a significant global health concern, contributing to substantial morbidity and mortality among women. Hormone receptor-positive (HR+)/HER2-negative (HER2-) breast cancer constitutes a considerable proportion of cases, and significant advancements have been made in its management. CDK4/6 inhibitors (CDK4/6is) are a new targeted therapy that has demonstrated efficacy in adjuvant, advanced and metastatic settings. The propensity of lobular breast carcinomas for estrogen-rich sites, such as periocular tissues and orbital fat, may explain their tendency for orbital metastases. Current treatment strategies for these cases are predominantly palliative, and the prognosis remains poor. This article presents a unique case of a 51-year-old female with progressive right periorbital edema, pain, and limited ocular motility. An imaging work-up showed bilateral intra and extraconal orbital infiltration, which was biopsied. The histopathologic analysis disclosed mild chronic inflammatory infiltrate with thickened fibrous tissue and moderately differentiated lobular carcinoma cells, positive for GATA3 and CK7 markers, with 100% of tumor nuclei expressing estrogen receptors (ER+). A systemic evaluation showed a multicentric nodular formation in both breasts. Further diagnostic assessments unveiled an HR+/HER2- bilateral lobular breast carcinoma with synchronous bilateral orbital metastases. Systemic treatment was initiated with abemaciclib 150mg twice daily and letrozole 2.5mg once a day. However, this regimen was interrupted due to toxicity. After two weeks, treatment was resumed with a reduced abemaciclib dose (100mg twice daily) alongside letrozole, with a reasonable tolerance. Nearly two years after the initial diagnosis of inoperable metastatic cancer, the patient remains on the same systemic treatment regimen with no signs of invasive disease. This case report is the first of a patient presenting with bilateral orbital metastases from bilateral lobular breast cancer, showing an impressive and sustained response to a first-line treatment regimen combining abemaciclib and letrozole. A literature review on bilateral orbital metastases from breast cancer is also presented.